Facile self-assembly of 2D metal-organic framework/MXene (Ni-MOF/Ti3C2) ultra-thin layered sheets for UV-light-based photocatalytic reaction - Radhalayam, D (ELSEVIER, 2026)
Photocatalytic technology has to aim to utilization to adopt green chemistry principles for environmental benign technology using renewable energy resources. Herein, the quest for metal/metal-oxide free co-catalysts, a 2D NiMOF/Ti3C2 MXene composite nanostructures was synthesized using a simple self-assembly technique. The structural features of prepared 2D Ni-MOF/Ti3C2 MXene was examined with X-ray diffraction analyses. Moreover, the morphological and structural features of prepared 2D Ni-MOF/Ti3C2 MXene were analyzed through transmission electron microscopy and selected area electron diffraction analyses. In addition to that, the chemical composition and elemental presence in 2D Ni-MOF/Ti3C2 MXene were determined with elementl mapping studies. The surface oxidation states of elements and their composition were studied with X-ray phtotelectron spectroscopic measurement. The photocatalytic activity of the composite Ni-MOF/Ti3C2 and pristine sample Ti3C2 were assessed by its ability to degrade the dye methyl orange under UV light exposure with H2O2. The degradation efficiencies of prepared Ni-MOF/Ti3C2 has performed 92 % and 86 % with the presence and absence of scavenger of H2O2, respectively. Furthermore, the prepared composite photocatalyst shown good stability and it was evident by reusability studies of five cycles with the degradation efficiency of 86 %. From results, the composite showcasing its potential usage in industrial applications in photocatalytic and energy conversion technologies.